Effects of vermicompost and lime on acidic soil properties and malt barley (Hordeum Distichum L.) productivity in Mecha district, northwest Ethiopia. - Zenebe Terefe; Tesfaye Feyisa; Eyayu Molla; Workineh Ejigu (PLoS ONE)
Due to continuous cultivation, high soil acidity, and low nutrient inputs, soil fertility depletion has been a major threat to northwest Ethiopia's crop productivity and food security. This study aimed to examine the effects of vermicompost and lime rates on soil properties and malt barley (Hordeum distichum L.) productivity under a furrow irrigation system on acidic soil in the Mecha district, northwest Ethiopia. The treatments were combinations of three levels of vermicompost (0, 2.66-, and 5.31-tons ha-1) and three levels of lime (0-, 2.16-, and 3.24-tons ha-1) arranged in a randomized complete block design with three replications. The results showed that the integrated application of 5.31 tons of vermicompost and 3.24 tons of lime ha-1 provided the highest soil pH (6.20), available phosphorus (8.55 mg kg-1), total nitrogen (0.25%), and organic carbon (3.40%). On the other hand, adding vermicompost and lime in combination or separately noticeably decreased the exchangeable acidity and aluminum toxicity. Besides, the integrated application of 5.31 tons vermicompost (VC) and 3.24 tons lime (L ha-1 provided the highest dry biomass (12.22 tons ha-1), grain yield (5.30 tons ha-1), and net benefit (197, 246 Ethiopian Birr (ETB). Overall, the integrated application of vermicompost and lime can substantially increase soil fertility and crop yields. However, this study needs further testing and validation at varied rates in other areas.